2017
DOI: 10.1016/j.jvs.2017.03.425
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular recanalization versus autogenous venous bypass for thromboangiitis obliterans patients with critical limb ischemia due to tibioperoneal arterial occlusion

Abstract: ER is a valid strategy for limb salvage in thromboangiitis obliterans patients who are unsuitable for bypass, contributing an acceptable amputation-free survival as high as with AVB, even though it is associated with lower patency rates and a higher rate of reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
(31 reference statements)
1
24
0
Order By: Relevance
“…It wasthus concluded that endovascular approach for tibial artery diseasewas a lower risk alternative to bypass with similar outcomes (5) .Similar study by Kaichung et all compared outcomes of endovascularrevascularisation versus venous bypass for tibioperoneal arterialocclusion and found that the amputation free survival for ER wassimilar to bypass but was associated with lower patency rate andhigher rates of reintervention (6) .Primary stenting is also an evolving option for infrapopliteadisease. It was found to reduce the risk of reinterventionandamputation , better wound healing, compared with plain balloonangioplasty with no negative impact on the mortality rates andRutherford class (7,8) . But issues of cost effectiveness, stent design,bare metal vs drug eluting stent are areas of debate and hencerequires further randomised control trails.…”
Section: Primary Patency Ratesmentioning
confidence: 95%
“…It wasthus concluded that endovascular approach for tibial artery diseasewas a lower risk alternative to bypass with similar outcomes (5) .Similar study by Kaichung et all compared outcomes of endovascularrevascularisation versus venous bypass for tibioperoneal arterialocclusion and found that the amputation free survival for ER wassimilar to bypass but was associated with lower patency rate andhigher rates of reintervention (6) .Primary stenting is also an evolving option for infrapopliteadisease. It was found to reduce the risk of reinterventionandamputation , better wound healing, compared with plain balloonangioplasty with no negative impact on the mortality rates andRutherford class (7,8) . But issues of cost effectiveness, stent design,bare metal vs drug eluting stent are areas of debate and hencerequires further randomised control trails.…”
Section: Primary Patency Ratesmentioning
confidence: 95%
“…All endovascular procedures were performed under local anesthesia as previously published [ 1 ]. For all bypass surgery procedures, the suitability of the inflow and outflow arterial anatomy was initially evaluated by means of CTA and/or DSA.…”
Section: Methodsmentioning
confidence: 99%
“…Amputation was classified as either major (above the ankle) or minor (below the ankle) [ 1 ]. The graft patency was assessed using imaging studies (DUS or CTA); primary patency was defined as the interval from the initial procedure until the repeat procedure or a major amputation of the index limb, whichever occurred first, and secondary patency was defined as the interval from the initial procedure until the graft occlusion or a major amputation of the index limb, regardless of the number of subsequent procedures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations